The proof in the cuban administrative process (Justice and Law, 2024)
The general theory of evidence in the administrative process is a less explored commonplace in the doctrine; however, the question acquires singular relevance as it is understood as the basis for resolving conflicts of this order, both in the procedures in charge of the Administration and in the judicial venue. This article deals with the essential aspects of evidence in this process, as a result of the new legislative scenario that the country presents, since the entry into force of Law No. 142 in 2022. These questions correspond to the analysis of the evolution of this area of law in Cuba, which also concerns the burden of proof after the procedural novelties, its evaluation and the role to be played by the judge in the evidential phase, as premises of the principle of effective judicial protection.
Keywords: Burden of proof; administration; proactivity; ex officio evidence